Fluorescent polymers for sensing and imaging - Uchiyama, Seiichi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nowadays, all scientists recognize that fluorescent probes play important roles in wide research areas, from chemistry to biology. By combining this fact with specific functional benefits from synthetic polymers, fluorescent polymeric probes are occasionally superior to small organic and inorganic fluorescent (or luminescent) probes in terms of sensitivity, robustness, and multiple functionality. The targets of fluorescent polymeric probes have extended from chemical species to physical parameter. This special issue is a platform for researches to develop a novel fluorescent polymeric probe and to establish a new analytical method using a conventional fluorescent polymeric probe. Related researches, e.g., fluorometric investigation of functional polymers, are also included.